Rekonstruksi Penegakan Hukum Terhadap Pelanggaran Kemitraan Perkebunan Sawit Dalam Hukum Persaingan Usaha Di Indonesia: REKONSTRUKSI PENEGAKAN HUKUM TERHADAP PELANGGARAN KEMITRAAN PERKEBUNAN SAWIT DALAM HUKUM PERSAINGAN USAHA DI INDONESIA - Wahyu Friyonanda Riza (Jurnal Media Justitia Nusantara, 2025)
The Palm oil plantation partnership collaboration often experiences problems for both parties involved in the collaboration, and on a large scale can threaten the sustainability of the partnership collaboration. This research aims to find out, explain and explain the model and concept of law enforcement against violations of oil palm plantation partnerships. This type of research is normative juridical legal research, namely an approach that refers to applicable laws and regulations. Meanwhile, in terms of its nature, this research is descriptive, meaning that it provides a clear picture of law enforcement regarding violations of palm oil plantation partnerships between companies and communities. This research provides an offer for Partnership Violation Law Enforcement to undergo transformation in order to realize certainty of fair law enforcement.